A forest canopy as a living archipelago: Why phylogenetic isolation may increase and age decrease diversity. (26th November 2018) - Hidasi‐Neto, Jose; Bailey, Richard I.; Vasseur, Chloe; Woas, Steffen; Ulrich, Werner; Jambon, Olivier; Santos, Ana M. C.; Cianciaruso, Marcus V.; Prinzing, Andreas
Abstract: Aim: An individual tree resembles a living island, a small spatially distinct unit upon which colonizers maintain populations. However, several differences exist compared to oceanic islands: a tree is relatively young, is composed of numerous differently aged branches, may be phylogenetically isolated from neighbours, and some of its colonizers are specific to particular tree lineages. We suggest that these specificities strongly affect both alpha‐ and beta‐diversity within trees, including positive effects of isolation on the diversity of generalists, and strengthening of the effect of isolation with tree age. Location: Rennes, Bretagne, Western France Taxon: Little‐dispersive, generalist oribatid mites (Acari) and highly dispersive, specialist gall wasps (Hymenoptera: Cynipidae) on oak ( Quercus sp.) trees. Methods: We tested the effects of tree and branch age, tree and branch habitat diversity, and tree phylogenetic isolation on per‐branch and per‐tree alpha‐diversity, and on within‐tree beta‐diversity of both taxonomic groups. Results: For gall wasps, no variable explained diversity patterns at any level. In contrast, for oribatid mites, we found that high phylogenetic isolation of trees and high branch age increased alpha‐diversity per tree and per branch (in young trees) as well as turnover among branches. High tree age decreased alpha‐diversity per branch (in phylogenetically isolated trees) and increased turnover among branches. Increasing habitat diversity increased alpha‐diversity per tree, but decreased alpha‐diversity per branch (in young trees). Main conclusions: For mites, contrary to common expectation, we suggest that: (a) phylogenetically distant neighbours are a source of immigration of distinct species and (b) with the increase of tree age, species‐sorting results in a few species colonizing and dominating their preferred patches. In gall wasps, strict specialization on oaks, and efficient dispersal may render oak age or isolation unimportant. The positive relationship between isolation and within‐tree turnover is a new contribution to biogeography in general.